CEMARAN ASPERGILLUS FLAVUS DAN AFLATOKSIN PADA RANTAI DISTRIBUSI PRODUK PANGAN BERBASIS JAGUNG DAN FAKTOR YANG MEMPENGARUHINYA [Contamination of Aspergillus flavus and Aflatoxin at Distribution Chain of Maize Based Food Product and its Influencing Factors - Harsi D. Kusumaningrum; . Suliantari; Aris D. Toha; Sindhu H. Putra; Aldilla S. Utami (Jurnal Teknologi dan Industri Pangan, 2010)
Aflatoxin is a human carcinogen, produced by fungus Aspergillus flavus that frequently contaminates maize. Analysis of A. flavus by plate counting and aflatoxin by Thin Layer Chromatography were performed on 104 samples and 25 samples, respectively, of maize grain and maize based food products from different places in Bogor-West Java, Boyolali-Central Java and Bojonegoro-East Java. These regions support significant number of maize production in Java. Forty percent of the samples were contaminated by A. flavus, whereas aflatoxin level of higher than 20 ppb was found in 4 of 25 samples. The highest contamination level of A. flavus was found at the collector trader that often stored the maize grain in average of 15 days, at room temperature. There was a significant correlation between the length of storage as well as relative humidity with the contamination levels of A. flavus. Significant correlation was also found between the contamination levels of A. flavus with the level of aflatoxin in maize grain. However, no significant correlation was found between the aflatoxin level and the contamination levels of A. flavus in the processed maize based food products.